Strengthening of basic competences in natural sciences from the Pedagogical Model of Integral Vocational Training in the National Center of Hospitality, Tourism and Food Industries, regional Bogotá (CNHTyA) - Quintana Arias, Ronald Fernando
This article gives an account on a work that sought to strengthen basic skills in natural sciences in the CNHTyA. Between 2017 and 2018, a descriptive study of a case study was carried out with a quantitative approach, designing and applying a learning guide for the development of basic skills in Natural Sciences. The strategies employed increased the skill level by 40%. The optimization of the development of competences was given by prioritizing the relationship of affective, cognitive and metacognitive levels in professional training, above psychometric principles.